Structural and phase change characteristics of inorganic microencapsulated core/shell Al–Si/Al2O3 micro-particles during thermal cycling. Issue 9 (November 2015) - He, Fei; Song, Guangping; He, Xiaodong; Sui, Chao; Li, Mingwei
Abstract: In this paper, the structural and phase change characteristics of Al–Si/Al2 O3 core/shell structure were investigated during thermal cycling from room temperature to 1000 °C by means of scanning electron microscopy (SEM), thermogravimetry (TG) and differential scanning calorimeter (DSC). The smooth and dense shells can maintain the integrity of core/shell structures during thermal cycling. The latent heat of the encapsulated Al–Si alloy reduces to 271.90 kJ/kg after 20 times thermal cycling. The experimental and calculative results between latent heat and mass increase were compared. The consumption of Al element in core/shell structures results in the latent heat reducing. The cracked ratio of the shells at different times of thermal cycling was estimated, the result of which is that the accumulative cracked ratio exceeds 20% after 20 times thermal cycling. The rupture of the shell is attributed to the thermal mis-match stress between the core and the shell. The crack at the interface can release serious thermal stress in thermal cycling.